2020
DOI: 10.1126/sciadv.aba6944
|View full text |Cite
|
Sign up to set email alerts
|

VapBC22 toxin-antitoxin system from Mycobacterium tuberculosis is required for pathogenesis and modulation of host immune response

Abstract: Virulence-associated protein B and C toxin-antitoxin (TA) systems are widespread in prokaryotes, but their precise role in physiology is poorly understood. We have functionally characterized the VapBC22 TA system from Mycobacterium tuberculosis. Transcriptome analysis revealed that overexpression of VapC22 toxin in M. tuberculosis results in reduced levels of metabolic enzymes and increased levels of ribosomal proteins. Proteomics studies showed reduced expression of virulence-associated proteins and increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 76 publications
1
42
0
Order By: Relevance
“…We have earlier reported that strains with deletions in either vapBC3 or vapBC4 or vapBC11 or vapC22 are attenuated for growth in comparison to the wild type strain in guinea pigs and mice ( Agarwal et al, 2018 , 2020 ; Deep et al, 2018 ). The reduced expression of latency associated genes and genes belonging to the DosR regulon suggests that VapC21 might also be important for M. tuberculosis to establish infection in host tissues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have earlier reported that strains with deletions in either vapBC3 or vapBC4 or vapBC11 or vapC22 are attenuated for growth in comparison to the wild type strain in guinea pigs and mice ( Agarwal et al, 2018 , 2020 ; Deep et al, 2018 ). The reduced expression of latency associated genes and genes belonging to the DosR regulon suggests that VapC21 might also be important for M. tuberculosis to establish infection in host tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have shown that both MazF and VapC ribonucleases contribute to the ability of M. tuberculosis to establish infection in host tissues. These studies suggested that TA systems such as MazF3, MazF6, MazF9, VapBC3, VapBC4, VapBC11, and VapC22 enable M. tuberculosis to adapt to changes associated with the onset of host adaptive immunity ( Tiwari et al, 2015 ; Agarwal et al, 2018 , 2020 ; Deep et al, 2018 ). Despite the reduced expression of genes belonging to the dormancy regulon or latency associated antigens in the mutant strain, we did not observe any significant differences in the lung bacillary loads in mice infected with various strains until 8 weeks post-infection.…”
Section: Discussionmentioning
confidence: 99%
“…Among those genes unrelated to antimicrobial resistance, we found several components of toxin-antitoxin systems, including vapC29, vapB3, vapC35, vapB40, vapC22 , and vapC47 , which are critical for the adaptation of bacteria to different stressful conditions. For example, VapC22 has a significant role in virulence and innate immune responses in particular 40 . Other significant virulence regulators in MTBC are the two-component systems (2CS), which are critical players in extended transcriptional networks.…”
Section: Resultsmentioning
confidence: 99%
“…However, they have been associated with protection against phage infection or stabilization of genomic regions (Pecota and Wood, 1996;Fraikin et al, 2020;Peltier et al, 2020). In addition, they also contribute to the virulence and persistence of pathogenic bacteria in vivo in infection models (Helaine et al, 2014;Lobato-Márquez et al, 2016;Agarwal et al, 2020).…”
mentioning
confidence: 99%
“…A substantial number of M. tuberculosis toxins have been cloned and showed toxicity when expressed in E. coli or in mycobacteria (Ramage et al, 2009;Sala et al, 2014;Agarwal et al, 2018;Akarsu et al, 2019). Besides, transcription of several M. tuberculosis TA systems were shown to be induced under various stress conditions including drug exposure, hypoxia, heat-shock, DNA damages (Sala et al, 2014;Tiwari et al, 2015;Gupta et al, 2017;Agarwal et al, 2018), and gene deletion mutants ΔvapC22, ΔvapBC3/4/11 and ΔmazF3/6/9 are strongly impaired in host infection (Tiwari et al, 2015;Agarwal et al, 2018;Deep et al, 2018;Agarwal et al, 2020). Even though transcriptional induction of TA systems does not necessarily reflect toxin activation (LeRoux et al, 2020), these data suggest that toxins could modulate bacterial growth depending on environmental conditions, and thus contribute to M. tuberculosis physiology and virulence (Sala et al, 2014).…”
mentioning
confidence: 99%